Poetry Writing and Reading Training Using Picture Media for Teachers and Students of SB. Aisyiyah Kampung Pandan, Malaysia - Mubarok, Insani; Rachmawati, Dian Karina; Ngatmain (English Education Department - Universitas Nasional Karangturi, 2024)
Learning children's literature through writing and reading poetry, a child can express life experiences and learn to express various problems and how to deal with them. Through learning literature one can get entertainment and pleasure. Besides that, through literature in the form of poetry, one can have politeness in language, because literary works are so rich in words that are arranged precisely and charmingly. The method used in this service is the presentation of the speakers in the form of exposure to various stages of techniques for writing children's poetry and also simulations or direct practice with the participants, followed by questions and answers and discussions then assessed by the teacher.